Advanced framework for practical and clinical outcome based learning in optometry / Ai-Hong Chen and Azmir Ahmad - Chen, Ai-Hong; Ahmad, Azmir (2021)
Frustrations can be caused by the mismatch between teachers’ and learners’ expectations leading to ineffective communication. Ineffective communication can complicate the learning environment, and the consequences are often underestimated. Bloom’s Taxonomy has been widely used in the educational context to improve communication concerns, and optometry education is no exception. However, the implementation of outcome-based learning in Optometry predominantly from the practical and clinical perspectives remains indefinable. This conceptual paper is to postulate an advanced framework for outcome-based teaching and learning in Optometry. First, the overview of the three-phase progression in optometry outcome-based learning is presented with the emphasis on the respective subdomain in cognitive, psychomotor and affective domains. Then, outcome-based learning is elaborated further specifically from practical and clinical skill teaching perspectives. Receiving phenomena, remembering and understanding of facts are predominant in the theory-teaching phase. Responding to phenomena, application, conceptualization, visualization, verbalization, and practice are prevalent in the practical skill teaching phase. In the clinical teaching phase, the cognitive domain aims at the analysing-evaluating-creating level. This is aligned to the valuing-organization-internalizing value levels in the affective domain and the correction and reinforcement-skill mastery-skill autonomy level in the psychomotor domain. Four-competency classification in optometry clinical teaching is elaborated with the respective domains in outcome-based learning. The taxonomy plays a scaffolding structural supportive role to ensure that the educational process is corroborated in systemic, more manageable entities, without discouraging expansion of application and theory that may not fit the taxonomy